Journal of management
The Journal of Organizational Behavior aims to publish empirical reports and theoretical reviews of research in the field of organizational behavior, wherever in the world that work is conducted. The journal will focus on research and theory in all topics associated with organizational behavior within and across individual, group and organizational levels of analysis.